Sosialisasi Aplikasi Pengaduan Masyarakat Terkait Kondisi Lingkungan Pada Yayasan Peduli Lingkungan Kota Sorong - Muhammad Rizki Setyawan; Muh Fadli Hasa; Rendra Soekarta; Aprisa Rian Histiarini; Rinanda Tri Setiawan (LPPM Universitas Harapan Bangsa Purwokerto, 2022)
The Sorong environmental care foundation is a non-governmental organization dedicated to environmental sustainability, particularly in the areas of waste, reforestation, water and air pollution and plant and wildlife investigations in Sorong City. In the process of resolving complaints, it is still by telephone or WhatsApp, and due to lack of staff sometimes complaints are not recognized and are not processed by the foundation. Therefore, community service activities were carried out with partners, namely the Sorong City Environmental Care Foundation to help solve the problems faced. Where this activity is divided into 4 stages, namely data collection, application design and manufacture, socialization and implementation and evaluation. The conclusion obtained is that this activity can be said to take place very well and successfully. This can be seen from the results of the questionnaire and the positive response from the foundation and the community regarding this activity. The results achieved are that the Sorong City Environmental Care Foundation has an Android-based mobile application that can make it easier for the public when they want to make a complaint and a website that makes it easier for the foundation to recap data on complaints that have been made by the community.